Evaluating the Impact of a Training Program in Shared Decision-Making for Neurologists Treating People with Migraine - Porta-Etessam, J.; Santos-Lasaosa, S.; Rodríguez-Vico, J.; Núñez, M.; Ciudad, A.; Díaz-Cerezo, S.; Comellas, M.; Pérez-Sádaba, F. J.; Lizán, L.; Guerrero-Peral, A. L. (Neurology and therapy, 2023)
Introduction Migraine symptoms vary significantly between patients and within the same patient. Currently, an increasing number of therapeutic options are available for symptomatic and preventive treatment. Guidelines encourage physicians to use shared decision-making (SDM) in their practice, listening to patients’ treatment preferences in order to select the most suitable and effective therapy. Although training for healthcare professionals could increase their awareness of SDM, results concerning its effectiveness are inconclusive. This study aimed to analyze the impact of a training activity to promote SDM in the context of migraine care. This was addressed by evaluating the impact on patients’ decisional conflict (main objective), patient-physician relationship, neurologists’ perceptions of the training and patient’s perception of SDM. Methods A multicenter observational study was conducted in four highly specialized headache units. The participating neurologists received SDM training targeting people with migraine in clinical practice to provide techniques and tools to optimize physician-patient interactions and encourage patient involvement in SDM. The study was set up in three consecutive phases: control phase, in which neurologists were blind to the training activity and performed the consultation with the control group under routine clinical practice; training phase, when the same neurologists participated in the SDM training; and SDM phase, in which these neurologists performed the consultation with the intervention group after the training. Patients in both groups with a change of treatment assessment during the visit completed the Decisional conflict scale (DCS) after the consultation to measure the patient’s decisional conflict. Also, patients answered the patient-doctor relationship questionnaire (CREM-P) and the 9-item Shared Decision-Making Questionnaire (SDM-Q-9). The mean ± SD scores obtained from the study questionnaires were calculated for both groups and compared to determine whether there were significant differences ( p < 0.05). Results A total of 180 migraine patients (86.7% female, mean age of 38.5 ± 12.3 years) were included, of which 128 required a migraine treatment change assessment during the consultation (control group, n = 68; intervention group, n = 60). A low decisional conflict was found without significant differences between the intervention (25.6 ± 23.4) and control group (22.1 ± 17.9; p = 0.5597). No significant differences in the CREM-P and SDM-Q-9 scores were observed between groups. Physicians were satisfied with the training and showed greater agreement with the clarity, quality and selection of the contents. Moreover, physicians felt confident communicating with patients after the training, and they applied the techniques and SDM strategies learned. Conclusion SDM is a model currently being actively used in clinical practice for headache consultation, with high patient involvement in the process. This SDM training, while useful from the physician's perspective, may be more effective at other levels of care where there is still room for optimization of patient involvement in decision-making.